The inhibitory activity of ginsenoside Rp4 in adenosine diphosphate-induced platelet aggregation - Son, Young-Min (J Ginseng Res, 2017)
BACKGROUND: Korean ginseng, Panax ginseng Meyer, has been used as a traditional oriental medicine to treat illness and promote health for several thousand years. Ginsenosides are the main constituents for the pharmacological effects of P. ginseng. Since several ginsenosides, including ginsenoside (G)-Rg3 and G-Rp1, have reported antiplatelet activity, here we investigate the ability of G-Rp4 to modulate adenosine diphosphate (ADP)-induced platelet aggregation. The ginsenoside Rp4, a similar chemical structure of G-Rp1, was prepared from G-Rg1 by chemical modification. METHODS: To examine the effects of G-Rp4 on platelet activation, we performed several experiments, including antiplatelet ability, the modulation of intracellular calcium concentration, and P-selectin expression. In addition, we examined the activation of integrin αIIbβ(3) and the phosphorylation of signaling molecules using fibrinogen binding assay and immunoblotting in rat washed platelets. RESULTS: G-Rp4 inhibited ADP-induced platelet aggregation in a dose-dependent manner. We found that G-Rp4 decreased calcium mobilization and P-selectin expression in ADP-activated platelets. Moreover, fibrinogen binding to integrin αIIbβ(3) by ADP was attenuated in G-Rp4-treated platelets. G-Rp4 significantly attenuated phosphorylation of extracellular signal-regulated protein kinases 1 and 2, p38, and c-Jun N-terminal kinase, as well as protein kinase B, phosphatidylinositol 3-kinase, and phospholipase C-γ phosphorylations. CONCLUSION: G-Rp4 significantly inhibited ADP-induced platelet aggregation and this is mediated via modulating the intracellular signaling molecules. These results indicate that G-Rp4 could be a potential candidate as a therapeutic agent against platelet-related cardiovascular diseases.